Impact of Mitochondrial Fatty Acid Synthesis on Mitochondrial Biogenesis - Nowinski, Sara M.; Van Vranken, Jonathan G.; Dove, Katja K.; Rutter, Jared (Current biology, 2018)
Biology students today are taught that mitochondria are ‘the powerhouse of the cell’. This gross over-simplification of their cellular role has arguably led to a paucity of knowledge concerning the many other tasks carried out by this multifunctional organelle. Mitochondrial fatty acid synthesis (mtFAS) is one such under-appreciated pathway that is crucial for mitochondrial function, although even mitochondrial experts are often surprised to learn of its existence. For many years, the only function of mtFAS was thought to be the production of lipoic acid, an important co-factor for several mitochondrial enzymes. However, recent advances have revealed a far wider role for mtFAS in mitochondrial physiology. The discovery of human patients with mutations in mtFAS enzymes has brought renewed interest in understanding the full significance of this novel mode of mitochondrial metabolic regulation. We now appreciate that mtFAS is a nutrient-sensitive pathway that provides an elegant mechanism whereby acetyl-CoA regulates its own consumption via coordination of lipoic acid synthesis and tricarboxylic acid (TCA) cycle activity, iron–sulfur (FeS) cluster biogenesis, assembly of oxidative phosphorylation complexes, and mitochondrial translation. In this minireview, we describe and build upon the important discoveries that led to our current understanding of this elegant mechanism of coordination of nutrient status and metabolism. In this minireview, Nowinski et al. highlight the various roles of mitochondrial fatty acid synthesis in mitochondrial physiology and discuss recent studies implicating this pathway in the coordination of nutrient status and metabolism.